2014
DOI: 10.1016/j.jacc.2014.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Results and Safety of Common Interventional Procedures in Congenital Heart Disease

Abstract: Contemporary community practice, procedural outcomes, and safety for 6 common congenital interventional procedures are reported. These benchmarks may be compared with individual center results and historical single-center and multicenter results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 23 publications
7
69
1
2
Order By: Relevance
“…Major and total adverse event rates were 1.6% and 7.2%, both significantly smaller than after surgical repair. The subsequent IMPACT Registry and MAGIC study reported similar success and complication rates [42,43]. ASO embolization is the most frequent adverse event as reported by the FDA Manufacturer and User Facility Device Experience database, accounting for 51% of events with a rate of 0.2-1.1%.…”
Section: Amplatzer Septal Occluder (Aso)mentioning
confidence: 85%
“…Major and total adverse event rates were 1.6% and 7.2%, both significantly smaller than after surgical repair. The subsequent IMPACT Registry and MAGIC study reported similar success and complication rates [42,43]. ASO embolization is the most frequent adverse event as reported by the FDA Manufacturer and User Facility Device Experience database, accounting for 51% of events with a rate of 0.2-1.1%.…”
Section: Amplatzer Septal Occluder (Aso)mentioning
confidence: 85%
“…Though quantifying its incidence has proved challenging, the current most conservative estimates of the risk of erosion appears to be 1 in 1000 9, 28 , from which an unknown fraction develop life-threatening tamponade. The risk of procedure-associated death in isolated TC-ASD in published series are 0–0.15%(30,34,35). The best estimates of risk-adjusted procedural mortality following O-ASD, as derived from the Society for Thoracic Surgeons Congenital Heart Surgeons Database, are between 3–9 per 1,000(5,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Though natural history studies demonstrate that patients with large ASD left untreated have dramatically reduced lifespan(42,43), to our knowledge, there is no evidence that early intervention produces dramatically different results in terms of any clinical outcome. There are multiple series that demonstrate that ASD can be closed in young patients(30,34,35,41), and conventional wisdom holds that closure of ASD surgically does not depend on patient size in a meaningful way. It is unclear what the impetus is for the trend towards progressively earlier intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Die häufigsten Maßnahmen im Herzkatheterlabor betreffen Verschlüsse von Atriumseptumdefekten (ASD), Eingriffe am persistierenden Ductus arteriosus (PDA), im Aortenisthmus, an den Pulmonalarterien (PA) sowie an der Aorten-und Pulmonalklappe [21]. Der vorliegende Beitrag bietet hinsichtlich der häufigsten Eingriffe eine Übersicht über die aktuelle Situation, den State of the Art, die Grenzen sowie die Entwicklung und wesentlichsten Trends in der interventionellen Kinderkardiologie.…”
Section: Hintergrundunclassified